INCIDENCE OF MUSTARD APHID (LIPAPHIS ERYSIMI KALT.) IN ARID ZONE - AWASTHI, CHANDRA JYOTSNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Based on infestation index, the population of L. erysini found directly related to the abiotic parameters which include temperature, relative humidity and cloudy weather.